Analysis of Hospital Without Wall Service Quality at Dr. Iskak Tulungagung Hospital With Donabedian’s Model - Krisnha Dian Ayuningtyas; Saiful Bukhori; FX Ady Soesetijo (Jurnal Manajemen Kesehatan Indonesia, 2023)
dr. Iskak Tulungagung hospital made a healthcare service innovation during Covid-19 pandemic. This innovation called as hospital without wall to reduce the Covid-19 transmission. This program provides overall health services integrating pre-, intra-, inter-, and post-hospital care services through the Public Safety Center (PSC) platform. Authors examine the implementation of a hospital without walls in post-hospital aspect by using Donabedian's Model to improve service quality. The independent variables are facility and waiting time. The dependent variable is satisfaction. The intervening variable is patient perception. Assessment using a Likert scale questionnaire with a value range of 1-5. Descriptive data analysis used SPSS 25 and multivariate analysis used SMARTPLS 3.0. Our 96 respondents are very satisfied with this service but had to wait for a long time until the nurse arrived at home. Our analysis showed that facility variable affects the waiting time so that is affects patient satisfaction. This program has good structure so it makes a good process and satisfaction. Waiting time significantly associated with facility.